2005
DOI: 10.1086/431582
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Sidereal Anisotropy of Galactic Cosmic-Ray Intensity Observed by the Tibet Air Shower Array

Abstract: We present the large-scale sidereal anisotropy of galactic cosmic-ray intensity in the multi-TeV region observed with the Tibet-III air shower array during the period from 1999 through 2003. The sidereal daily variation of cosmic rays observed in this experiment shows an excess of relative intensity around 4 ∼ 7 hours local sidereal time, as well as a deficit around 12 hours local sidereal time. While the amplitude of the excess is not significant when averaged over all declinations, the excess in individual d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 21 publications
(34 reference statements)
8
70
0
Order By: Relevance
“…the lower energies, where cosmic rays follows adiabatically the magnetic field lines, and the higher energies, where the heliospheric influence starts to become subdominant. This is in general agreement with the energy dependence of the anisotropy amplitude that increases up to about 10 TeV and decreases above this energy (Amenomori et al, 2005). Resonant scattering may be able to redistribute the 10 −3 interstellar anisotropic component of the cosmic ray arrival distribution, depending on particle energy and pitch angle, and on the properties of heliospheric magnetic field inside the tail and on the heliopause.…”
Section: Heliospheric Influence On Tev Cosmic Rayssupporting
confidence: 85%
See 2 more Smart Citations
“…the lower energies, where cosmic rays follows adiabatically the magnetic field lines, and the higher energies, where the heliospheric influence starts to become subdominant. This is in general agreement with the energy dependence of the anisotropy amplitude that increases up to about 10 TeV and decreases above this energy (Amenomori et al, 2005). Resonant scattering may be able to redistribute the 10 −3 interstellar anisotropic component of the cosmic ray arrival distribution, depending on particle energy and pitch angle, and on the properties of heliospheric magnetic field inside the tail and on the heliopause.…”
Section: Heliospheric Influence On Tev Cosmic Rayssupporting
confidence: 85%
“…These results show that the anisotropy matches the observations in the Northern Hemisphere and that a sudden change in its topology occurs at energy in excess of a few hundreds of TeV, confirming the observations by Aglietta et al (2009). The transition between the two anisotropy regimes is preceded by a steady decrease of the amplitude at particle energy above 10 TeV, following an increase trend at lower energies (see Amenomori et al, 2005 for instance). The global anisotropy cannot be described with a simple dipole, but as a superposition of spherical harmonic contributions, where statistically significant small angular scale features, with amplitude of order 10 −5 -10 −4 , are also observed (Abbasi et al, 2011;Santander et al, 2013a), in agreement with similar observations in the Northern Hemisphere (Amenomori et al, 2007;Abdo et al, 2008;Bartoli et al, 2013;BenZvi et al, 2013), as shown in Fig.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…From an observational point of view, a statistically significant anisotropy has been observed by a variety of experiments, sensitive to different energy ranges (from tens of GeV to a few PeV), located on or below the Earth's surface in the Northern Hemisphere (Nagashima et al 1998;Hall et al 1999;Amenomori et al 2005Amenomori et al , 2006Amenomori et al , 2011Guillian et al 2007;Abdo et al 2009;Aglietta et al 2009;Zhang et al 2009;Munakata et al 2010;Cui et al 2011;de Jong et al 2011;Bartoli et al 2015) and in the Southern Hemisphere (Abbasi et al 2010(Abbasi et al , 2011(Abbasi et al , 2012Aartsen et al 2013Aartsen et al , 2016.…”
Section: The Problem Of Anisotropies and Corresponding Approachesmentioning
confidence: 99%
“…Recently, due to greatly improved observational methods, the direct observation of S i A has become possible in the high-energy region by observations with cosmic ray and gamma-ray detectors (e.g. Amenomori et al, 2004Amenomori et al, , 2005Guillian et al, 2007;Abdo et al, 2008;Abbasi et al, 2010). This method is, however, not applicable to S i A in the lower energy region as cosmic rays cannot maintain their direction hindered by the influence of the heliomagnetic and geomagnetic fields.…”
Section: Introductionmentioning
confidence: 99%